PENINGKATAN KUALITAS PELAPORAN KEUANGAN UMKM - Muis, Nurhasni; Alam, Syamsul; Daud, Dahniyar; Eldi, Eldi; Razak, Nurlaely (Universitas Negeri Makassar, 2024)
The purpose of this community service activity is to assist micro, small, and medium enterprises (MSMEs) in enhancing their financial knowledge and skills, thereby improving the quality of financial reporting for MSME business units in Sanrobone Village, Sanrobone Subdistrict, Takalar Regency. This activity was conducted over a one-day period, involving 15 MSME participants who are residents of Sanrobone Village, Takalar. The methods employed included lectures, tutorials, and discussions. The results of this community service program showed that MSME participants were able to carry out bookkeeping tasks, such as recording cash inflows and outflows, in accordance with generally accepted principles. Additionally, participants gained an understanding of cash receipts and disbursements, sales and purchases, and the preparation of financial statements. However, due to the limited duration of the activity, the training's impact on improving the productivity of MSME participants was not maximized. Therefore, it is planned to conduct ongoing training accompanied by mentoring to further enhance the quality of financial reporting, which will also positively impact the productivity of MSME products.